If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(-1) = z Multiply -1 * -1 1 = z Solving 1 = z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. 1 + -1z = z + -1z Combine like terms: z + -1z = 0 1 + -1z = 0 Add '-1' to each side of the equation. 1 + -1 + -1z = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1z = 0 + -1 -1z = 0 + -1 Combine like terms: 0 + -1 = -1 -1z = -1 Divide each side by '-1'. z = 1 Simplifying z = 1
| 2cos(3x-1)=0 | | 32=2(x+4.5) | | (c^2-9c-5)-(-c^2-8c-10)= | | (x-4)2=(x-2)2 | | x^2-10*x+13=0 | | x^2-10*x+13= | | 7v-28=9+3v-1 | | (11b^2-7)+(15b^2-b)= | | (6y-8)+(5y-3)+(6y+4)=180 | | 50=.5*20V^2 | | -26.3+0.1p=0.9+5.3 | | 2y-5x=-8 | | x*x+4x+1=32 | | -12.1+0.5p=0.9+5.3 | | ln^5+ln(2x)=5 | | -[4(7)-(14(7)+8)]=8+(9(7)+7) | | 6+(-10)+(-2)+8= | | -12.1+.5=0.9p+5.3 | | -12+.5=0.9p+5.3 | | 3c+12=6c+11.31 | | 3c+12=6c+12.31 | | -5-2=1-2x+3x | | 2.3x+1.37=-11.74 | | -[4z-(14z+8)]=8+(9z+7) | | -91.9+n=-99 | | 0=-u+u | | -8(t-2)-(t+3)=10 | | 7y=21x+14 | | 3r-5(12)=-22 | | 0.7x-0.6x+1=4 | | -10y+18=15y+13 | | -10y+18=15y+13-8 |